Voice of Islamic moderation from the Malay world - M. Kamal Hassan (Emerging Markets Innovative Research (EMIR), 2011)
This is a book written by an independent an non-partisan Muslim Malay academic, mainly for a non-Muslim audience in mind, either in Malaysia or overseas. It is also addressed to the Muslim leaders, intelligentsia, professionals an students who are interested in the issue of peaceful coexistence of the Muslim world and the West.